From 'here and now' to there and then : the evaluation of the effectiveness of Ehlers and Clark's model for treating PTSD in a rape survivor - Davidow, Amy (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
The purpose of this research is to document the response of a rape survivor to a treatment based on Ehlers and Clark's (2000) therapy model and to use the material to evaluate the effectiveness of this kind of therapy in the South African context. In so doing, the specific local cultural and contextual factors, which may affect the overall effectiveness of the treatment, will be highlighted and discussed.
Keywords: Post-traumatic stress disorder -- Treatment -- South Africa; Rape trauma syndrome -- Treatment -- South Africa; Psychotherapy -- South Africa; Cognitive therapy